Experimental Study on the Effect of Initial Water Content and Temperature Gradient on Soil Column Segregation Frost Heave - Dong Zhang; Meng Wang; Xiao-kang Li; A-qiang Liu (Geofluids)
A series of freezing experiments were carried out on the Qinghai silty clay using a one-dimensional soil column particle image velocimetry (PIV) system. The effects of the initial water content and temperature gradient on the frost heave of the soil column were analysed. The experimental results show that the total volumetric water content after the Qinghai silty clay freezing is much greater than the initial water content before freezing, and the total volumetric water content at the segregated layer reaches the maximum value. The average unfrozen water content firstly increases sharply with time and then decreases slowly. The obvious horizontal layered segregation cracks filled with unsaturated needle-columnar ice lenses have occurred above the soil column frozen fringe. The thickness of segregated ice is about 43% of the total frost heave. There is a small frost heave in the frozen fringe and a small compression deformation amount in the unfrozen zone. Under the same temperature gradient conditions, the soil column with the low initial water content has a smaller frozen depth, larger total volumetric water content, more water intake, smaller segregated ice thickness, and less total frost heave amount than that of the soil column with the high initial water content. Under the same initial water content conditions, the soil column with a large temperature gradient has a greater frozen depth, consistent total volumetric water content, larger segregated ice thickness, and greater total frost heave amount than that of the soil column with a small temperature gradient.